Research and Development (R & D) Sebagai Pilar Utama dalam Membangun Ekonomi Industri Pertahanan Indonesia - Endro Tri Susdarwono (Politeknik Negeri Cilacap, 2020)
This study intends to describe how defense research and development, which is a major pillar, is used to accelerate efforts towards independence in the economy of the Indonesian defense industry. This research is qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. At present, almost all countries that provide large-scale military equipment are supported by strong research capacity and domestic technological capacity. Therefore, efforts to develop highly competitive defense technology with established support are essential. Not only to face security threats but also to make Indonesia relevant in the fierce competition in the era of economic globalization ahead. The country can reap optimum benefits from its defense industry activities. In addition to strengthening war machines and arsenal, most of the research and development activities also encourage the use of research results for commercial or non-military industrial activities. The pattern of a symbiosis of military technology mutualism for use in the general public (commercial) has recently become a reference for policy developers known as the concept of dual-use technologies. The concept of dual-use technologies is then applied in the form of tiered trees that describe the roots of for a product or technology in general that must be developed and then grow like branches and branches to specific specifications for military or commercial use.